Pengaruh Customer Experience dan Brand Trust terhadap Customer Loyalty - Dirbawanto, Nana Dyki; Sutrasmawati, Rr Endang (Management Analysis Journal, 2016)
Customer loyalty become the most important thing that every company must be considered to keep their customer. One thing that company can do on case to keep their customer loyalty is increase the customer experience and brand trust. The purpose of this research is to know how customer ecperience and brand trust affect customer loyalty either parsially or simultanly.Population of this study is all visitors of MATS Store Semarang. The sample size was determined through purposive judgment sampling method, with 116 respondents (n=116) as total sample. Data were gathered through questionnaires adapting Likert scale. On this research, as independent variable are customer experience and brand trust, and as dependent variable is customer loyalty. Analysis of data using multiple linier regression and descriptive analysis.The result of this research shows. The result of this research shows that the value of Fhitung3.869 with taraf significant 0.024 < 0.05. The thing prove customer experience and brand trust affect customer loyalty simultanly.In conclusion, the study suggests that Customer Experience has effects on customer loyalty, while Brand Trust does not affect customer loyalty. Based on the research findings, this study suggests Mats Store management to improve and develop their brand trust strategies in order to increase customers’ confidence products sold and distributed by MATS Store.